Phototactic Response of Two Spotted Cricket (Gryllus bimaculatus De Geer) to Electric Bulb Light Colours and Types - Timothy, Chukwu A; Emmanuel, Okrikata (International Journal of Sustainable Agricultural Research, 2020)
This study examined the phototactic response of two spotted cricket (G. bimaculatus) to incandescent and LED bulb light of different colours. Light traps fitted with 25 Watts incandescent bulbs and 3 Watts Light Emitting Diode (LED) of different colours (red, yellow, green, blue and white) were used. Also included was a control trap. The traps were operated from 1800hr to 2400hr. G. bimaculatus collected were counted and the data subjected to variance analysis. Student Newman Keul’s test was used to separate significantly different means at 5% level of probability. Relationship between light intensity and insect density was assessed by correlation and linear regression analysis. Results indicated that LED had higher mean intensity despite lower wattage and that, Blue colour had the highest mean intensity (736.80 Lux) among the LEDs and white (1094.20 Lux) among the incandescent bulbs. Statistical analysis showed that differences in attractiveness among LED bulb colours were due to random variation (p = 0.17); however was significant (p < 0.001) among incandescent bulbs. Of the total G. bimaculatus collected attracted, 93.7% was by LED bulbs with blue LED bulb alone attracting 57.1%. Light intensity was positively and significantly correlated with density of G. bimaculatus attracted for both LED (r = 0.92, R2 = 84.4%) and incandescent (r = 0.96, R2 = 92.5%) bulbs. Higher attraction of G. bimaculatus to blue coloured LED bulbs could be attributed to preference and/or high light intensity. Blue LED bulbs of higher intensity can thus be used to manipulate G. bimaculatus for man’s benefit.